Precision measurements of Higgs couplings: Implications for new physics scales - Englert, Christoph; Plehn, Tilman (Journal of physics. G, Nuclear and particle physics, 2014)
The measured properties of the recently discovered Higgs boson are in good agreement with predictions from the Standard Model. However, small deviations in the Higgs couplings may manifest themselves once the currently large uncertainties will be improved as part of the LHC program and at a future Higgs factory. We review typical new physics scenarios that lead to observable modifications of the Higgs interactions. They can be divided into two broad categories: mixing effects as in portal models or extended Higgs sectors, and vertex loop effects from new matter or gauge fields. In each model we relate coupling deviations to their effective new physics scale. It turns out that with percent level precision the Higgs couplings will be sensitive to the multi-TeV regime.
Gesehen am 07.05.2015